Estudio de factibilidad para la creación de una empresa consultora y asesora en proyectos de inversión para las MIPYMES de la ciudad de Machala. - Pineda Guzmán, Aldo (2015)
The aim of this study was to determine the feasibility that would implement a consulting firm and Advisor Investment Projects (ECAPI) for MSMEs, the city of Machala, taking into account the need for micro en¬trepreneurs who do not have spaced or resources to solve their business problems. The research, descriptive and non-experimental design, allowed to observe the phenomena as they occur today with bibliographic research bases, documentary and developing surveys, to obtain information and processing. Market varia-bles, production costs, availability of capital resources, financial evaluation and profitability for statistical, bibliographic and economic analysis were established, the results show the need and opportunity to think in a company to assist and advise MSMEs following methodology well organized to ensure favorable results in the positioning of the companies while to settle in a highly competitive job market. The financial analysis showed positive feasibility has ECAPI on the market, as projected revenues cover project costs, leaving a substantial profit and a stable liquidity.